Electronically Controllable Varactor Loaded Beam Switchable 4-Element Array Antenna for Sub-6 GHz Application - Pooja Panda; Rohit Mathur; Ashutosh Mahajan (IEEE Access)
In this paper, we present a 4-element varactor loaded switched beam array antenna, which is configured using a switch-line phase shifting mechanism and varactor diodes in the Sub-6 GHz band ranging from 5.8 to 6.6 GHz. A discrete beam steering at $± ~30{^{°}}$ is aimed to achieve by employing switch-line phase shifters into the feed, whereas a continuous beam steering around $± ~30{^{°}}$ is accomplished by using varactor diodes. The one-to-four-way corporate feeding network is used for the array which is connected through an aperture-coupled feeding system. The design is first validated using HFSS (High-Frequency Structure Simulator), confirming the discrete beam steering at $± ~24{^{°}}$ , with continuous steering possible between $± ~22{^{°}}$ and $± ~30{^{°}}$ . The discrete steering is found to be in agreement with measurements showing steering of +26° and -28°, which were close to its simulated outcomes i.e., $± ~24{^{°}}$ . The performance of this design, validated by HFSS simulations and “anechoic chamber” measurements are found in good agreement, with the broadside beam gain of 7.02 dBi with a Front-to-Back ratio of 17.71 dBi. This design can serve itself as a good candidate as a sub-unit for 5G base stations through hybrid beam forming.